The Difference Between Internet and Social Networking Use among Ninth Graders - Mesa, Shean Kenneth Lee P.; Soliman, Janel L.; Cudia, Myvin Angela; Cruz, Dennis Henry A.; Cogayan, Veniz Laine; Licup, J Ann; Naguit, Mark Steven; Cabrera, Jericho; Lising, Erikalyn; Galang, John Renus F. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study aims to dive into ninth-grade students' internet and social networking experiences, examining both intrapersonal and interpersonal components. The study used a mixed-method sequential explanatory design to incorporate quantitative and qualitative methodologies, with a strong emphasis on ethical considerations. In the quantitative phase, data is collected using standardized questionnaires, which were then analyzed and examined statistically to find occurring patterns and trends from the feedback given by the ninth graders. Following that, the qualitative phase includes in-depth interviews to contextualize and explain the quantitative results from the first phase of the study. The findings provide complex insights into the participants' attitudes and behaviors around internet usage and social networking. While most people believe that the internet is mostly entertaining and convenient, there are differing opinions regarding the presence of its impact on academic performance and mental well-being. This study concludes that there is no substantial difference in internal and social networking experiences between male and female students. The findings highlight the complex nature of ninth graders' Internet and social networking experiences, including knowledge acquisition, social communication, and emotional regulation. Recommendations include encouraging responsible and ethical digital citizenship and offering support tools to help students navigate the online environment securely and successfully, while also developing literacy. Overall, this study contributes to a better knowledge of how young individuals engage with and how significant individuals are influenced by the digital landscape, providing valuable information for educational institutions and policymakers looking to create positive internet experiences among night graders students.